2018
DOI: 10.1111/jmft.12353
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Functional Family Therapy (FFT) as an Intervention for Youth Probationers in Singapore

Abstract: Family functioning is predictive of youth recidivism in Singapore. However, there is a lack of family based interventions for youth offenders on community probation. Evidence-based family interventions developed in Western populations, such as Functional Family Therapy (FFT), have been found to be effective in mitigating subsequent youth criminal behavior. However, no study has examined whether such interventions can be implemented and adapted for use in Eastern cultures. Thus, this paper sought to detail the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 54 publications
0
15
0
10
Order By: Relevance
“…This is a particular important distinction within the local context considering the family circumstances and parenting were found to be the biggest predictor of recidivism in youth offenders (Chu et al, 2015), and that family dysfunctionality as well as criminality were associated with youth offenders being arrested and charged at a younger age (Chng, Chu, Zeng, Li, & Ting, 2016). To address this aspect, implementing targeted interventions such as the Functional Family Therapy may be useful in improving (a) the family functioning of the youth probationers, (b) the interactions between the youth probationers and their parents, as well as (c) reducing the psychological distress within their families—these have been shown to have impact on longer-term outcomes in other jurisdictions (see, e.g., Aos et al, 2011; Gan, Zhou, Hoo, Chong, & Chu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is a particular important distinction within the local context considering the family circumstances and parenting were found to be the biggest predictor of recidivism in youth offenders (Chu et al, 2015), and that family dysfunctionality as well as criminality were associated with youth offenders being arrested and charged at a younger age (Chng, Chu, Zeng, Li, & Ting, 2016). To address this aspect, implementing targeted interventions such as the Functional Family Therapy may be useful in improving (a) the family functioning of the youth probationers, (b) the interactions between the youth probationers and their parents, as well as (c) reducing the psychological distress within their families—these have been shown to have impact on longer-term outcomes in other jurisdictions (see, e.g., Aos et al, 2011; Gan, Zhou, Hoo, Chong, & Chu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the center reported a reduction in risk level from moderate to low (13.0 to 5.8, respectively) on the Youth Level of Service assessment, demonstrating the FFT's success in a Scandinavian context (Mørkrid & Christensen, ). In a recent effort to implement FFT within an Eastern cultural context (e.g., Singapore), Gan et al, () reported similar rates of engagement, dropout, and total number of sessions as compared to the United States (i.e., California) and New Zealand, demonstrating the transportability of the program across multiple cultural contexts.…”
Section: Family Therapymentioning
confidence: 99%
“…Cultural influences may have contributed to underreporting of family‐related difficulties. One of the major challenges faced by FFT therapists in Singapore was the unwillingness of clients to be candid about negative feelings toward other family members at the beginning of therapy (Gan et al., 2018 ). Specifically, it was observed that families tended to deny or trivialize conflicts and negative emotions, especially during the first session.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information relating to therapist selection, training, supervision, and performance assessment has previously been documented (Gan et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation